KONTAMINASI DIRI DALAM SENI LUKIS - RAHMAT ADE PUTRA, Yasrul Sami, S.Sn, M.Sn, Ady Rosa (Serupa The Journal of Art Education, 2014)
Contamination is a process where the outside elements come tothings that it is not should be and it is created a new uncommon formin a material, in a physics form even nature. This final works facedmany processes to go through and inspired by the unusual possessesthat experienced by the writer himself especially at college level. Asthe artist of these paintings, the writer hopes the entire devotee canenjoy this works in any condition. These paintings belong tocontemporary art that made reference to the observation,contemplation and then visualized it into lines, color and the formthat needed. And also supported by the tool and substances consideras artistic value which become the main elements in each work.Kata kunci : kontaminasi diri, seni, lukis.